Romeo and Juliet - Shakespeare, William, 1564-1616; Bloom, Harold (Shakespeare, William, 1564-1616. Works. 2003., 2004)
Shakespeare's 'Romeo and Juliet' is perhaps the most read and beloved of all stage works. This annotated version of the play makes it completely accessible to readers in the 21st century.